Increasing Screening for Intimate Partner Violence and Reproductive Coercion: Understanding Provider Motivations. (September 2021) - Burton, Candace W.; Carlyle, Kellie E.
Current estimates indicate that as few as 2% of health providers may be universally screening patients or clients for intimate partner violence and reproductive coercion. Barriers to screening have been well-described in the literature; however, little attention has been paid to the factors that motivate providers to carry out screenings. This study explored data from a sample of providers who had received specific screening and intervention training to ascertain what factors motivated them to complete screenings in practice. Patient-related, provider-related, and work setting factors were identified. Findings may support improved provider training and, ultimately, screening rates.